Analysis of the antimicrobial activity of Lactobacillus plantarum YM-4-3: implications of suitable conditions for extending the shelf life of fermented soybean products. Issue 9 (29th August 2019) - Liu, Chen-Jian; Luo, Ming-Yue; Li, Qiang-Kun; Deng, Gang; Li, Xiao-Ran; Yang, En; Luo, Yi-Yong
Abstract : The shelf life of fermented soybean products is extended following combination treatment with Lactobacillus plantarum and low concentration sodium chloride. Abstract : Lactobacillus ( Lb. ) plantarum is typically used as a starter culture in salt-fermented foods. Here we report 3–4% NaCl reducing the antimicrobial activity of Lb. plantarum strain YM-4-3, owing to the decrease of bacterial growth, plantaricin activity and expression levels of plantaricin biosynthesis-related genes (PBGs). Meanwhile, 1% NaCl promoted slightly the growth of YM-4-3 and up-regulated the expression of PBGs to the greatest level. The results from a spoilage experiment of fermented soybean products revealed that the 1% NaCl and YM-4-3 treatment group had the longest shelf life representing the minimum number of pathogenic bacteria and the lowest degree of mildew. Therefore, a combination of Lb. plantarum with a low concentration of salt, such as 1% NaCl, is a recommended condition for preparing fermented foods.